Fast platelet recovery is associated with remission in primary immune thrombocytopenia - Gür Hatip, Fatma; Özbalcı, Demircan; Alanoğlu, Emine Güçhan; Hatip, Ahmet Yunus (The European Research Journal, 2023)
Objectives: We aimed to reveal predictors of response and response duration to steroid therapy in first line of treatment in immune thrombocytopenia (ITP). Methods: Fifty patients, who were diagnosed with ITP in hematology department of Suleyman Demirel University Hospital between 2005-2019, who had sufficient clinical and laboratory data, followed up for at least one year and received corticosteroid treatment in first line, were evaluated retrospectively for treatment response time, remission, prognosis on their first line treatment. The patients who maintained remission for more than 12 months was defined as group 1 and those who did not achieve remission or relapsed in less than 12 months were defined as group 2. Results: Twenty-two (44%) patients responded in first 3 days of the treatment, 16 (32%) patients in 4 to 7 days and 4 (8%) patients responded in more than 7 days. Eighty-four percent (n = 42) of these patients had complete response to corticosteroid treatment. When the remission maintenances were examined, it was observed that 22 (44%) patients were in remission for more than 12 months, 20 (40%) patients were in remission with treatment but relapsed before 12 months and 8 (16%) patients did not respond to corticosteroid treatment. When the response time to treatment in patients with or without remission was compared, remission was significantly lower in those who responded late to treatment (p = 0.01). When the response rates to corticosteroid treatment of patients in group 1 and 2 were evaluated, it was found that the response time to treatment was not related to the maintenance of remission (p = 0.267). Conclusions: Faster response time to treatment produced higher remission rates but, we could not find any relationship between response time to treatment and duration of remission.